Assessing the Impact of Desert Locust Infestation on Crops, Pasture and Livestock Health in Eastern Equatoria State, South Sudan - Yuga, Mario; Wani, Philip (European Journal of Applied Sciences, 2022)
Desert locust is the word’s dangerous migratory pest that destroys crops and pasture posing a major threat to food security and livelihoods for many rural populations that depend on agriculture. Understanding the level of damage caused by desert locust infestation and its impact on food and nutrition security among the farming communities is vital for the government and development partners to avail support to the affected populations to recover from the shock. The rapid assessment was carried out using household survey questionnaire tool to gather information on the impact of desert locust infestation on crops, pasture, and livestock health in the hotspots of Magwi, Kapoeta, Torit and Ikotos Counties of Eastern Equatoria State. The data gathered was analysed using Microsoft excel and SPSS version 23. The survey results showed that crop production is the main source of livelihood for the rural populations of the State, 20% of the households interviewed estimated a 15% reduction in cereal yields in the second season of 2020 compared to 5% losses in the normal cropping season of 2019. About 60% of the respondents said a few areas ranging from 10-25% of pastureland had been infested in the State. Approximately 26.7% of the respondents said livestock body conditions had been affected by the pasture loss. Therefore, encouraging farmers to diversify crop production is recommended. Training farmers in good agricultural practices and stronger disaster preparedness such as prepositioning of quality seeds in the event of disaster will help the smallholder farmers to recover from the locust crisis and improve their ability to withstand future shocks and natural disasters.